The things we keep - Hepworth, Sally (St. Martin's Press, 2016)
"Anna Forster, in the early stages of Alzheimer's disease at only thirty-eight years old, knows that her family is doing what they believe to be best when they take her to Rosalind House, an assisted living facility. She also knows there's just one another resident her age, Luke. What she does not expect is the love that blossoms between her and Luke even as she resists her new life at Rosalind House. As her disease steals more and more of her memory, Anna fights to hold on to what she knows, including her relationship with Luke. When Eve Bennett is suddenly thrust into the role of single mother she finds herself putting her culinary training to use at Rosalind house. When she meets Anna and Luke she is moved by the bond the pair has forged. But when a tragic incident leads Anna's and Luke's families to separate them, Eve finds herself questioning what she is willing to risk to help them"--